The Effect Of Training With Mini Games On Some Biochemical Indicators For Football Players Under The Age Of 17 Years - Benchebha, Tariq; Sadek, Ismail (sports creativity, 2025)
The study aimed to know the effect of training with mini games on some biochemical indicators (red blood cells, lymphocytes and eosinophil cells), the researcher adopted the experimental approach, and the study population represented in football players a category less than 17 years for the department of Bou- Saada, the sample was chosen. Intentionally, which was represented by 16 players from Amal Bou Saada team of less than 17 years, where the researcher designed a training program consisting of 24 unites and was applied to the individuals of the sample, and after collecting data by laboratory analyzes and statistically processing we reached the following results: Training leads With mini-games to increase the number of red blood cells, lymphocytes, and the number of eosinophil cells